The protective effect of resveratrol on vascular aging by modulation of the renin–angiotensin system. (March 2018) - Kim, Eun Nim; Kim, Min Young; Lim, Ji Hee; Kim, Yaeni; Shin, Seok Joon; Park, Cheol Whee; Kim, Yong-Soo; Chang, Yoon Sik; Yoon, Hye Eun; Choi, Bum Soon
Abstract: Background and aims: This study evaluated the effects of resveratrol on arterial aging and the renin–angiotensin system (RAS) in mice and vascular smooth muscle cells (VSMCs). Methods: Aging mice were divided into control and resveratrol groups. Histological changes, inflammation, oxidative stress, RAS components, and the expression of AMP-activated protein kinase (AMPK), silent information regulator T1 (SIRT1), peroxisome proliferator-activated receptor-γ co-activator 1α (PGC-1α), and anti-oxidative enzymes was measured in thoracic aortas of 24-month-old mice. The effect of resveratrol on fibrosis, cell senescence, and RAS components was also investigated in VSMCs stimulated by angiotensin (Ang) II. Results: Aorta media thickness, inflammation, fibrosis, and oxidative stress were significantly lower in the resveratrol group than in the control group. Resveratrol treatment decreased serum Ang II level and the aortic expression of prorenin receptor (PRR) and angiotensin converting enzyme (ACE), and increased serum Ang-(1–7) level and the expression of ACE2, Ang II type 2 receptor (AT2R), and Mas receptor (MasR). Resveratrol increased the expression of phosphorylated AMPK, SIRT1, PGC-1α, phosphorylated endothelial nitric oxide synthase and superoxide dismutase 1 and 2, and decreased that of NADPH oxidase 2 and 4. In Ang II-stimulated VSMCs, resveratrol treatment markedly decreased the number of senescence associated β-galactosidase stained cells and pro-fibrotic protein expression and increased the expression of AT2R and MasR. Conclusions: Resveratrol protects against arterial aging and this effect is associated with reduced activity of the PRR–ACE–Ang II axis and stimulation of the ACE2–Ang-(1–7)–ATR2–MasR axis. Highlights: Resveratrol protected against arterial aging by attenuating inflammation and oxidative stress. Resveratrol reduced the activity of the prorenin receptor-angiotensin converting enzyme-angiotensin II axis in aorta of aging mice. Resveratrol stimulated the activity of the angiotensin converting enzyme 2-angiotensin-(1–7)-angiotensin II type 2 receptor-Mas receptor axis both in vivo and in vitro .